JICA LOAN ASSISTANCE TOWARDS INDONESIA'S ECONOMIC EFFORTS AMID THE COVID-19 PANDEMIC - Tiara Putih Bastian; Hilmi Rachman Ibrahim (Journal of Social Political Sciences, 2023)
This research aims to analyze the role of the Japan International Cooperation Agency (JICA) in Indonesia's economic recovery efforts during the COVID-19 pandemic using the conceptual framework of the Interdependence theory. Qualitative research methods are employed to delve into the adaptive decision-making processes within Indonesia's economic policies. The findings highlight the interdependent steps taken in Indonesia's economic policies and assess the effectiveness of JICA's financial assistance in facilitating a gradual economic recovery. The study depicts the crucial role of JICA as a catalyst for interdependent changes, supporting Indonesia's economic recovery efforts amid the challenges posed by COVID-19. The implications of this research provide insights for decision-makers, emphasizing the effectiveness of interdependent decision-making in crisis management. Understanding the role of external assistance, such as JICA's support, becomes crucial for designing adaptive and effective economic recovery strategies. Overall, this research contributes to a nuanced understanding of Indonesia's economic response to the pandemic, offering practical insights for future crisis management and recovery efforts within the context of Interdependence theory.